Long‐Term Temporal Scale‐Dependent Warming Effects on the Mass Balance in the Dongkemadi Glacier, Tibetan Plateau. Issue 20 (14th October 2020) - Liang, Liqiao; Cuo, Lan; Liu, Qiang
Abstract: Understanding how climate change impacts glaciers is important in predicting their prospective response and crucial in forecasting water supplies and potential influences within surrounding lowland areas. This study evaluated annual, seasonal, and monthly warming effects on the mass balance in the Dongkemadi (DKMD) Glacier throughout 1960–2009. Results showed an increasing trend in annual, seasonal, and monthly scale air temperature variation: high during the cool season (0.0347°C a −1 ) and low during the warm season (0.0222°C a −1 ). Warming rates variability effects at all three scales were roughly the same. Seasonal and monthly warming rates produced roughly the same effect on glacier mass balance, while the annual warming rate overestimated annual mass balance by 20.0%. July produced the largest monthly warming effect overestimation at an annual warming rate (11.9 mm w.e.; 29.3%), followed by August and June. Furthermore, increases in annual melt energy (approximately 70%) throughout the study period primarily resulted from increases in net radiation and turbulent heat flux, which mainly occurred during the warm season (>96%). Proportional increases in warming‐induced rainfall caused a decrease in mass balance while contributing to differing warming rate effects through reductions in mass inputs and albedo rather than through increases in rain‐induced heat flux. Results confirmed the effectiveness of using seasonal scale warming rates to investigate warming effects on glacier and meltwater changes in the Dongkemadi Glacier. This study provides valuable information to accurately evaluate warming effects on energy/mass balance of glaciers worldwide. Key Points: Seasonal warming rates were suitable in accurately describing warming effects on the Dongkemadi Glacier mass balance throughout 1960–2009 Increases in annual melt energy largely resulted from a combined increase in net radiation and turbulent heat flux during the warm season Decreases in snowfall proportion resulting from warming contributed to decreases in mass balance